Frequency‐comb spectroscopy of the hydrogen 1S‐3S and 1S‐3D transitions. Issue 7 (17th May 2013) - Peters, Elisabeth; Yost, Dylan C.; Matveev, Arthur; Hänsch, Theodor W.; Udem, Thomas; Blaum, Klaus; Müller, Holger; Severijns, Nathal
Abstract An observation of the 1S‐3S and 1S‐3D two‐photon transitions in an atomic hydrogen beam using direct frequency‐comb spectroscopy in a Doppler‐free arrangement is reported. The measurements of these transition frequencies may be used for an improved determination of the Rydberg constant and the 1S Lamb shift and could shed light on the current discrepancy in the determination of the proton charge radius. Concurrently, a frequency comb well‐suited for high‐precision, Doppler‐free spectroscopy in the deep ultraviolet (DUV) wavelength region is demonstrated.